Wood and leaf anatomy of Copaifera langsdorffii dwarf trees - Longui, Eduardo Luiz; Costa, Natalia O.; Cielo-Filho, Roque; Marcati, Carmen Regina [UNESP]; Romeiro, Diego; Rajput, Kishore Shankarsinh; Lima, Israel L.; Florsheim, Sandra Monteiro Borges (Brill Academic Publishers, 2014)
There are various parameters that affect tree height and may cause dwarfism. Our goal was to study the anatomical variations in the leaf and xylem structure in dwarf and normal trees of Copaifera langsdorffii and their correlation with physico-chemical properties of the soils. Trees from two spatially close but different vegetation types, transitional forest and rupestrian field, showed markedly different wood and leaf characteristics. Adult trees of C. langsdorffii show normal height (up to 25 m) in transitional forests while in the rupestrian field they show dwarfism (small trees up to 2.5 m tall). Physical soil characteristics (such as rocky crust, low water availability due to shallow soil) presumably limit root growth and affect the rate of photosynthesis, which consequently affect the extension growth of the plant. Compared to normal trees, C. langsdorffii dwarf trees are characterized by narrow vessels and a higher proportion of vessels in multiples, features of the water transport system/hydraulic structure known to prevent embolism, wider rays with a greater potential to store starch, and higher stomatal density and potential conductance index.
Keywords: Ecological anatomy; Dwarfism; Plant strategies; Rupestrian field; Tropical woods